Small Palm Oil Plantation as Political Arena: Environmental Narratives Among Workers and NGOs in Aceh, Indonesia - Giulia Zaninelli (IAFOR Journal of Cultural Studies, 2020)
This contribution examines the different environmental visions surrounding small palm oil plantations in the province of Aceh, Sumatra, Indonesia. How are natural resources conceptualized by small-scale owners, workers and local environmentalists? How is the small palm oil plantation a political space? Which narratives take place in/on small palm oil plantations? From one point of view, workers and small owners tend to read the small palm oil plantation as a place of possibilities for the future, and it is configured as a place in which individual and collective agencies are negotiated continuously. From another point of view, environmentalists and NGO activists describe workers through the stereotyped lens of ignorance, rebellion and project appropriation. In Aceh, environmental awareness is strongly shaped by class, age, residency and educational background. Starting from an analysis of Italian public discourses about palm oil in 2015/2016, the author spent 4 months, from August to November 2016 getting rid of an ethnographic research in the province of Aceh. Through observations, data collection, questionnaires, and structured and semi-structured interviews, the author was able to explore and illustrate the characteristics of small oil plantations as a political arena and the daily life of small-scale owners, workers and environmentalists.